QEEG as a Novel Parameter of Neuroplasticity in Elderly with Mild Cognitive Impairment - Martina Wiwie Setiawan Nasrun; La Febry Andira Rose Cynthia; Nurhadi Ibrahim; Zenik Kusrini; Khamelia Malik; Wanarani Alwin (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2022)
Neuroplasticity is the ability of the brain to change structurally and functionally in compensation for changes related to age or disease. In elderly people, the most common neuroplasticity problem is mild cognitive impairment (MCI). MCI is a syndrome defined as a decrease in cognitive function that is not appropriate for a person's age and educational level. One way to minimize the progress of deterioration in MCI is by doing physical exercise, such as walking. In this study, participants did physical activity by walking at least 4000 steps/day for 3 months. Cognitive function was measured by brain wave parameters with Quantitative Electroencephalography (QEEG). Electroencephalography (EEG) signals were recorded before and after the intervention. The EEG results showed that the QEEG wave parameters after the intervention increased in the alpha frequency band and decreased in the delta frequency band.